Accelarated Orthodontic Treatment Using Microosteoperforations: A Comparative Study - Avirachan Tara V; Thomas Paul V; Kuruvilla Leelamma; Majithia Parag S; Paul Mithun (Wolters Kluwer Medknow Publications, 2024)
BackgroundAccelerated orthodontic treatment has gained popularity in recent years as patients seek shorter treatment durations. Microosteoperforations (MOPs) have emerged as a minimally invasive technique to expedite tooth movement. This study aims to compare the effectiveness of MOPs in accelerating orthodontic treatment with conventional methods. Materials and MethodsA randomized controlled trial was conducted on 60 orthodontic patients requiring dental alignment. The participants were divided into two groups: Group A (MOPs) and Group B (conventional orthodontic treatment). In Group A, MOPs were performed at the beginning of the treatment. Both groups received monthly orthodontic adjustments. Treatment duration, rate of tooth movement, and patient discomfort were measured and compared between the two groups. ResultsThe study found that in Group A, the treatment duration was reduced by 30% compared to Group B (P < 0.05). The rate of tooth movement in the MOPs group was 1.5 times higher than the conventional group (P < 0.01). Additionally, patient-reported discomfort levels were similar between the two groups. No adverse events related to MOPs were observed during the study. ConclusionMOPs significantly accelerate orthodontic treatment, reducing treatment duration by 30% and increasing the rate of tooth movement by 1.5 times compared to conventional methods. Importantly, MOPs are well-tolerated by patients, making them a valuable option for expediting orthodontic treatment with minimal discomfort. This study highlights the potential benefits of integrating MOPs into orthodontic practice to improve treatment efficiency and patient satisfaction.